2010
DOI: 10.1186/1471-2407-10-679
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug interactions and duplicate prescriptions among ambulatory cancer patients: a prevalence study using an advanced screening method

Abstract: BackgroundThe pharmacotherapeutic treatment of patients with cancer is generally associated with multiple side-effects. Drug interactions and duplicate prescriptions between anti-cancer drugs or interactions with medication to treat comorbidity can reinforce or intensify side-effects.The aim of the present study is to gain more insight into the prevalence of drug interactions and duplicate prescriptions among patients being treated in the outpatient day care departments for oncology and hematological illnesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 21 publications
0
21
1
2
Order By: Relevance
“…Another study that focused on pharmacokinetic interactions affecting the activity of the anticancer agent found a 5% prevalence rate [20]. Other studies found similar [10,16,17] or higher [19,21] rates of DIs, but the interactions considered were not limited to DIs with anticancer agents.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study that focused on pharmacokinetic interactions affecting the activity of the anticancer agent found a 5% prevalence rate [20]. Other studies found similar [10,16,17] or higher [19,21] rates of DIs, but the interactions considered were not limited to DIs with anticancer agents.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the risk of DIs in cancer patients is important to consider and has been the object of several studies [16,17,18,19,20,21,22]. A recent systematic review found that approximately one third of ambulatory cancer patients had potential DIs, but only limited data were found on the clinical consequences of DIs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Literature showed that drug interactions occur in approximately 30% of patients in an oncology outpatient clinic; therefore, with an accuracy of 5% and 95% CI, a total of 300 patients is considered appropriate 4 12 13…”
Section: Methodsmentioning
confidence: 99%
“…Second, many css are elderly, and altered drug metabolism in this age group might make them more susceptible to adverse drug interactions 10,19,20 . Third, css frequently take concomitant prescription and overthe-counter (otc) medications for the management of either other comorbidities or late toxicities from anticancer therapies 9,17,19,21,22 . For instance, one U.S. study of css found that 96% consumed at least 1 prescription drug, and 71%, at least 1 otc drug, 3 days before their chemotherapy 23 .…”
Section: Discussionmentioning
confidence: 99%